Steel material, electromagnetic iron core, electromagnetic contactor, method for manufacturing steel material and method for manufacturing electromagnetic iron core

JP2025030885APending Publication Date: 2025-03-07FUJI ELECTRIC CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023136562
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0009】 本発明の一態様によれば、高い硬度を有する鋼材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030885000001_ABST
    Figure 2025030885000001_ABST
Patent Text Reader

Abstract

To provide a steel material having high hardness.SOLUTION: A steel material includes a nitrided layer provided on the surface. The nitrided layer includes a first layer constituted of at least one kind of Fe4N, Fe2-3N and CrN, a second layer having a nitrogen concentration of 3 at% or more and 30 at% or less and a third layer having a nitrogen concentration of 0.2 at% or more and less than 3 at%, sequentially provided from the surface. A structure from an interface between the first and second layers to a depth of 15 μm includes martensite having an area rate of 90% or more to a rectangular area of 15 μm×200 μm in a cross section vertical to the surface.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel material, an electromagnetic core, an electromagnetic contactor, a method for manufacturing a steel material, and a method for manufacturing an electromagnetic core. [Background technology]

[0002] Steel materials are widely used in various machine parts, dies, etc., and methods for improving the surface hardness by infiltrating nitrogen into the surface are applied for the purpose of improving the wear resistance. Specific examples of such methods include gas nitriding, salt bath nitriding, ion nitriding, and plasma nitriding.

[0003] In particular, the steel material used for the electromagnetic core of the electromagnetic contactor is required to have high wear resistance. The electromagnetic cores of the electromagnetic contactor are provided in pairs facing each other, and as the electromagnetic cores collide with each other during opening and closing operations, the contact surfaces that come into contact with each other due to the collision wear out. As the wear of the contact surfaces of the electromagnetic cores progresses, the contact state of the electrical contacts of the electromagnetic contactor changes, resulting in opening and closing failure.

[0004] For example, Patent Document 1 describes that in order to improve the wear resistance of the contact surface of an electromagnetic core, the contact surface is hardened by a salt bath nitriding method. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-226118 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the electromagnetic core described in Patent Document 1, the structure and structure of the nitride layer are not considered, and the hardness may be insufficient for a steel material required to have high wear resistance for electromagnetic cores, etc.

[0007] In view of the above, an object of one aspect of the present invention is to provide a steel material having high hardness. [Means for solving the problem]

[0008] One aspect of the present invention is a steel material having a nitrided layer on a surface thereof, the nitrided layer including a first layer, a second layer, and a third layer, which are provided in this order from the surface, the first layer being made of Fe 4 N, Fe 2~3 The second layer has a nitrogen concentration of 3 at% or more and 30 at% or less, and the third layer has a nitrogen concentration of 0.2 at% or more and less than 3 at%, and the structure from the interface between the first layer and the second layer to a depth of 15 μm contains martensite with an area ratio of 90% or more relative to a 15 μm × 200 μm square region in a cross section perpendicular to the surface. Effect of the Invention

[0009] According to one aspect of the present invention, a steel material having high hardness can be provided. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a schematic diagram of a cross section of a steel material according to one embodiment. [Diagram 2] FIG. 2 is a perspective view of an electromagnetic core according to one embodiment. [Diagram 3] 1 is a cross-sectional view of an electromagnetic contactor according to one embodiment. [Figure 4] 5A to 5C are schematic diagrams for explaining a method of manufacturing an electromagnetic core according to one embodiment. [Diagram 5] 1 is a graph showing the relationship between the depth from the surface of the electromagnetic core and the nitrogen concentration in the example. [Figure 6] 1 is a SEM image showing a cross section of an electromagnetic core according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the symbol "to" indicating a range of values ​​means that the values ​​before and after the symbol "to" include the lower limit and upper limit of the range.

[0012] <Steel> Fig. 1 is a schematic diagram of a cross section of a steel material 1 according to one embodiment. As shown in Fig. 1, a nitride layer 3 is provided on the surface of the steel material 1. In other words, the surface of the steel material 1 is a nitrided surface. The nitride layer 3 includes a first layer 31, a second layer 32, and a third layer 33, which are provided in this order from the surface of the steel material 1.

[0013] The base material 2 of the steel material 1 is not particularly limited, but for example, a steel material having a carbon concentration of more than 0 mass% and not more than 0.7 mass% can be used. The base material 2 may further contain chromium and may be a steel material having a chromium concentration of more than 0 mass% and not more than 30 mass%. The region of the base material 2 shown in FIG. 1 means a portion of the base material in the same state as before the nitriding treatment. The base material 2 may be in the form of a plate, and may be an electromagnetic steel sheet.

[0014] The first layer 31 is formed on the outermost surface of the steel material 1 and is made of Fe 4 N, Fe 2~3 The first layer 31 is a nitrogen compound layer composed of at least one of N and CrN. The nitrogen concentration in the first layer 31 can be, for example, 20 at % or more.

[0015] The hardness of the first layer 31 is preferably 1000 Hv or more. This allows the steel material 1 to exhibit even better wear resistance. In this specification, the hardness means micro Vickers hardness, and can be measured using a micro Vickers tester in accordance with JIS Z2244. The hardness of the first layer 31 indicates the hardness at a position where the depth from the surface of the steel material 1 is 2 / 3 of the thickness of the first layer 31.

[0016] The first layer 31 preferably has a thickness of 1 μm or more. This allows the steel material 1 to have a higher hardness. The first layer 31 preferably has a thickness of up to 10 μm. This allows the steel material 1 to be prevented from becoming too hard and suffering brittle fracture.

[0017] The second layer 32 is formed on the base material 2 side of the first layer 31, and is a layer in which nitrogen is concentrated by diffusing and penetrating into the base material 2 through nitriding treatment. The nitrogen concentration in the second layer 32 is 3 at% or more and 30 at% or less. The steel material 1 has high hardness and can exhibit excellent wear resistance by having the second layer 32 with a nitrogen concentration of 3 at% or more and 30 at% or less.

[0018] The structure from the interface between the first layer 31 and the second layer 32 to a depth of 15 μm contains martensite with an area ratio of 90% or more relative to a 15 μm×200 μm square region in a cross section perpendicular to the surface of the steel material 1. The first layer 31 is a nonmetallic layer. By having the structure in the layer below the first layer 31 in addition to the first layer 31, the steel material 1 has high hardness and can be prevented from being brittle fractured due to excessive hardness. Therefore, the steel material 1 can exhibit excellent wear resistance. In particular, the steel material 1 can exhibit excellent wear resistance even when the steel material 1 is used in an electromagnetic core of an electromagnetic contactor and the steel materials 1 collide with each other repeatedly. Note that the depth means the distance in the direction perpendicular to the surface of the steel material 1.

[0019] Here, the area ratio of martensite can be calculated as follows. A square region of 15 μm×200 μm is observed at a magnification of 700 times with a scanning electron microscope (SEM) from the interface between the first layer 31 and the second layer 32 to a depth of 15 μm in a cross section perpendicular to the surface of the steel material 1, and the area ratio of martensite is calculated by performing image analysis on the photographed structure. In the SEM image, martensite is a portion that is lighter gray than other portions and has an acicular structure. In addition, in this specification, the interface means a virtual surface parallel to the surface of the steel material 1, which is obtained by averaging the uneven interface.

[0020] Specifically, the structure in the second layer 32 preferably contains martensite in an area ratio of 90% or more relative to a 15 μm×200 μm square region in a cross section perpendicular to the surface of the steel material 1. This allows the steel material 1 to have higher hardness and to be prevented from becoming too hard and causing brittle fracture. Thus, the steel material 1 can exhibit better wear resistance. In particular, even when the steel material 1 is used in an electromagnetic core of an electromagnetic contactor and the steel materials 1 collide with each other repeatedly, the steel material 1 can exhibit better wear resistance.

[0021] The second layer 32 is made of Fe 2~3 N, Fe 4 In this case, the second layer 32 may contain Fe 2~3 N, Fe 4 N or CrN is dispersed.

[0022] The second layer 32 preferably has a thickness of 1 μm or more. This allows the steel material 1 to have a higher hardness. The second layer 32 preferably has a thickness of up to 15 μm. This allows the steel material 1 to be prevented from becoming too hard and suffering from brittle fracture.

[0023] The hardness of the second layer 32 is preferably 420 Hv or more. This allows the steel material 1 to exhibit even better wear resistance. The hardness of the second layer 32 is more preferably 420 Hv or more and less than 1000 Hv. That is, the hardness of the second layer 32 is softer than the hardness of the first layer 31. This allows the steel material 1 to exhibit even better wear resistance while suppressing brittle fracture due to excessive hardness. Here, the hardness of the second layer 32 refers to the hardness at a position where the depth from the interface between the first layer 31 and the second layer 32 is 2 / 3 of the thickness of the second layer 32.

[0024] The third layer 33 is formed on the base material 2 side of the second layer 32, and is a layer in which nitrogen is diffused and infiltrated into the base material 2 by nitriding treatment, and has a lower nitrogen concentration than the second layer 32. The third layer 33 is made of γ-FeN 0.095The nitrogen concentration in the third layer 33 is equal to or greater than 0.2 at% and less than 3 at%. By having the third layer 33 with a nitrogen concentration of equal to or greater than 0.2 at% and less than 3 at%, the steel material 1 has high hardness and can exhibit excellent wear resistance.

[0025] The third layer 33 preferably has a thickness of 1 μm or more. This allows the steel material 1 to have a higher hardness. The third layer 33 preferably has a thickness of up to 45 μm. This allows the steel material 1 to be prevented from becoming too hard and suffering from brittle fracture.

[0026] The hardness of the third layer 33 is preferably 250 Hv or more and less than 420 Hv. That is, the hardness of the third layer 33 is softer than the hardness of the second layer 32. When the hardness of the third layer 33 is 250 Hv or more and less than 420 Hv, the steel material 1 can exhibit even better wear resistance and can be more prevented from being brittle fractured due to excessive hardness. Here, the hardness of the third layer 33 refers to the hardness at a position where the depth from the interface between the second layer 32 and the third layer 33 is 2 / 3 of the thickness of the third layer 33.

[0027] It is preferable that the hardness of the second layer 32 is 420 Hv or more, and the hardness of the third layer 33 is 250 Hv or more and less than 420 Hv. This allows the steel material 1 to exhibit even better wear resistance, and also makes it possible to prevent brittle fracture due to excessive hardness.

[0028] The steel material 1 may be in the form of a plate. This makes it possible to obtain a steel product of a desired thickness in which a desired number of steel materials 1 are laminated. When the steel material 1 is in the form of a plate, the thickness of the steel material 1 is not particularly limited, but can be, for example, 0.5 mm to 20 mm.

[0029] When the steel material 1 is in a plate shape, a nitride layer 3 may be provided on an end surface of the steel material 1. In other words, the end surface of the steel material 1 is a nitrided surface. The nitride layer 3 may include a first layer 31, a second layer 32, and a third layer 33, which are provided in this order from the end surface.

[0030] The steel material 1 may have magnetic properties. When the steel material 1 has magnetic properties, an electromagnetic iron core or an electromagnetic steel sheet made of the steel material 1 can be provided.

[0031] <Electromagnetic core> Fig. 2 is a perspective view of an electromagnetic core 10 according to one embodiment. As shown in Fig. 2, the electromagnetic core 10 of this embodiment is formed by laminating a plurality of plate-shaped magnetic steel materials 1 in the plate thickness direction. The plurality of steel materials 1 are fixed by pins 5. The steel materials 1 may have three protrusions arranged so that the shape in a plan view is E-shaped. The electromagnetic core 10 may be used as a fixed core, or may be used as a movable core arranged to face the fixed core and be freely movable.

[0032] The electromagnetic core 10 may have three protrusions 4a, 4b, and 4c that are provided so that the planar shape is E-shaped. The heights of the side protrusions 4a and 4b located on both sides are the same and are higher than the height of the central protrusion 4c located in the center. Here, the height means the height from the bottom surface 6 of the electromagnetic core 10. As a result, when the electromagnetic core 10 is a fixed core and a movable core, when the three protrusions 4a, 4b, and 4c are brought into contact with each other in an opposed manner, the side protrusions 4a and 4b come into contact with each other, but the central protrusions 4c do not come into contact with each other, so that a gap is formed between the central protrusions 4c. In other words, when the electromagnetic core 10 is a fixed core and a movable core, the side protrusions 4a and 4b include contact surfaces 7a and 7b that come into contact when the fixed core and the movable core come into contact, and the central protrusion 4c includes a non-contact surface 7c that does not come into contact when the fixed core and the movable core come into contact.

[0033] The difference in height between the side convex portions 4a, 4b and the central convex portion 4c is not particularly limited, but can be, for example, greater than 0 mm and equal to or less than 0.1 mm.

[0034] The surface of the steel material 1 constitutes the contact surfaces 7a, 7b of the electromagnetic core 10. That is, the contact surfaces 7a, 7b of the electromagnetic core 10 are provided with a nitride layer 3. The nitride layer 3 includes a first layer 31, a second layer 32, and a third layer 33, which are provided in this order from the contact surfaces 7a, 7b. The first layer 31 is made of Fe 4 N, Fe 2~3 The contact surfaces 7a, 7b are made of at least one of N and CrN, and the structure from the interface between the first layer 31 and the second layer 32 to a depth of 15 μm in each of the contact surfaces 7a, 7b contains martensite with an area ratio of 90% or more to a square region of 15 μm×200 μm in a cross section perpendicular to the contact surfaces 7a, 7b. Therefore, the contact surfaces 7a, 7b of the electromagnetic core 10 have high hardness, and can be prevented from becoming too hard and causing brittle fracture. As a result, the electromagnetic core 10 can exhibit excellent wear resistance even when the electromagnetic cores 10 collide with each other repeatedly. The nitride layer 3 does not need to be provided on the non-contact surface 7c of the electromagnetic core 10.

[0035] <Magnetic contactor> 3 is a cross-sectional view of an electromagnetic contactor 100 according to one embodiment. The electromagnetic contactor 100 of this embodiment has an electromagnetic core 10 of this embodiment.

[0036] The electromagnetic contactor 100 may further include a main body case 21 having a two-part structure consisting of an upper case 21a and a lower case 21b, a fixed contactor 22 fixedly arranged in the upper case 21a, and a movable contactor 23 arranged so as to be freely movable toward and away from the fixed contactor 22.

[0037] An electromagnetic core 10 that drives the movable contact 23 is disposed in the lower case 21b. The electromagnetic core 10 may include a fixed core 10A and a movable core 10B that is disposed movably opposite the fixed core 10A. The configurations of the fixed core 10A and the movable core 10B are similar to those of the electromagnetic core 10 described above.

[0038] An electromagnetic coil 28 wound around a coil holder 27 and supplied with single-phase AC is fixed to a central protrusion 15c (described later) of the fixed core 10A. A return spring 29 that biases the movable core 10B in a direction away from the fixed core 10A is disposed between the upper surface of the coil holder 27 and the base of a central protrusion 14c (described later) of the movable core 10B.

[0039] A contact holder 41 is connected to the upper end of the movable core 10B. This contact holder 41 is connected to the movable contact 23 arranged on its upper end side and is fixed to an insertion hole provided in the upper case 21a. The movable contact 23 is pressed downward by a contact spring 43 so as to obtain a predetermined contact pressure against the fixed contact 22 and is held there.

[0040] The fixed core 10A has contact surfaces 18a, 18b that come into contact when the fixed core 10A and the movable core 10B come into contact with each other. The surface of the steel material 1 that constitutes the fixed core 10A constitutes the contact surfaces 18a, 18b. The movable core 10B has contact surfaces 17a, 17b that come into contact when the fixed core 10A and the movable core 10B come into contact with each other. The surface of the steel material 1 that constitutes the movable core 10B constitutes the contact surfaces 17a, 17b. That is, a nitride layer 3 is provided on each of the contact surfaces 18a, 18b of the fixed core 10A and the contact surfaces 17a, 17b of the movable core 10B. The nitride layer 3 includes a first layer 31, a second layer 32, and a third layer 33 that are provided in this order on each of the contact surfaces 17a, 17b, 18a, 18b. The first layer 31 is made of Fe 4 N, Fe 2~3The contact surfaces 17a, 17b, 18a, and 18b are made of at least one of N and CrN, and the structure from the interface between the first layer 31 and the second layer 32 to a depth of 15 μm contains martensite with an area ratio of 90% or more to a square region of 15 μm×200 μm in a cross section perpendicular to the contact surfaces 17a, 17b, 18a, and 18b. Therefore, the contact surfaces 18a, 18b of the fixed core 10A and the contact surfaces 17a, 17b of the movable core 10B have high hardness, and can suppress brittle fracture due to excessive hardness. As a result, the electromagnetic contactor 100 can exhibit excellent wear resistance even when the fixed core 10A and the movable core 10B collide repeatedly.

[0041] The fixed core 10A may have three protrusions 15a, 15b, and 15c that are arranged to have an E-shape in plan view. The three protrusions include side protrusions 15a and 15b located on both sides and a central protrusion 15c located in the center. The side protrusions 15a and 15b may include contact surfaces 18a and 18b. That is, the contact surfaces 18a and 18b of the side protrusions 15a and 15b are each provided with a nitride layer 3. In this case, the central protrusion 15c is not provided with the nitride layer 3.

[0042] The fixed core 10A may have a shading coil 30 below the contact surfaces 18a, 18b of the side protrusions 15a, 15b. The shading coil 30 suppresses fluctuations in electromagnetic attraction force, noise, and vibration caused by changes in alternating magnetic flux in a single-phase AC electromagnet.

[0043] The movable core 10B may have three protrusions 14a, 14b, and 14c arranged to have an E-shape in plan view, similar to the fixed core 10A. The three protrusions include side protrusions 14a and 14b located on both sides and a central protrusion 14c located in the center. The side protrusions 14a and 14b may include contact surfaces 17a and 17b. That is, the contact surfaces 17a and 17b of the side protrusions 14a and 14b are each provided with a nitride layer 3. In this case, the central protrusion 14c is not provided with a nitride layer 3.

[0044] When the fixed core 10A and the movable core 10B come into contact with each other, the side protrusions 15a, 15b of the fixed core 10A come into contact with the side protrusions 14a, 14b of the movable core 10B, but the central protrusions 14c, 15c (the central protrusion 14c of the fixed core 10A and the central protrusion 15c of the movable core 10B) do not come into contact with each other. In other words, the central protrusion 15c of the fixed core 10A includes a non-contact surface 18c that does not come into contact when the fixed core 10A and the movable core 10B come into contact with each other, and the central protrusion 14c of the movable core 10B includes a non-contact surface 17c that does not come into contact when the fixed core 10A and the movable core 10B come into contact with each other. That is, the nitride layer 3 is not provided on the non-contact surface of the fixed core 10A and the non-contact surface of the movable core 10B.

[0045] When the fixed core 10A and the movable core 10B come into contact with each other, the central protrusions 14c and 15c of the fixed core 10A and the movable core 10B do not come into contact with each other, forming a gap between the central protrusions 14c and 15c. The gap serves to adjust the magnetic force acting between the fixed core 10A and the movable core 10B to an appropriate value. In a normal electromagnetic contactor, when the gap decreases due to wear of the contact surfaces of the fixed core and the movable core, the magnetic force acting between the fixed core and the movable core becomes larger than the appropriate value, which may cause opening and closing failure. In the electromagnetic contactor 100 of this embodiment, the nitride layer 3 is provided on the contact surfaces 18a and 18b of the side protrusions 15a and 15b of the fixed core 10A and the contact surfaces 17a and 17b of the side protrusions 14a and 14b of the movable core 10B, so that the contact surfaces 17a, 17b, 18a, and 18b have high hardness and can exhibit excellent wear resistance. Therefore, the electromagnetic contactor 100 can maintain the gap between the central protrusions 14c, 15c of the fixed core 10A and the movable core 10B, and can improve the life span.

[0046] Furthermore, of the fixed core 10A and the movable core 10B, the nitride layer 3 is provided only on the contact surfaces 17a, 17b, 18a, and 18b, and the nitride layer 3 is not provided on the non-contact surfaces 17c and 18c, which do not require wear resistance, so that the manufacturing costs of the fixed core 10A and the movable core 10B (electromagnetic core 10), as well as the electromagnetic contactor 100, can be reduced.

[0047] The movable contactor 23 has an elongated flat conductive portion 23a and movable contact portions 23b, 23c formed on the lower surface of both the left and right ends of the conductive portion 23a. An armature 42 made of a magnetic material is fixed to the upper surface of the central portion in the left-right direction of the conductive portion 23a by a fastening means such as adhesion. A contact spring 43 is disposed between the upper surface of the armature 42 and the lower surface of the insertion hole, and the contact spring 43 presses the movable contactor 23 downward.

[0048] The fixed contact 22 has a pair of fixed contact portions 22a, 22b facing the movable contact portions 23b, 23c of the movable contact 23, and a pair of elongated flat conductive portions 22c, 22d arranged parallel to the conductive portion 23a of the movable contact 23. External connection terminals 44a, 44b are connected to the outer ends of the conductive portions 22c and 22d. A yoke 46 made of a magnetic material facing the armature 42 is fixed to a fixed portion 45 between the conductive portions 22c and 22d in the upper case 21a.

[0049] Next, the operation of the electromagnetic contactor will be described. When the electromagnetic coil 28 is in a non-energized state, no electromagnetic attraction force is generated between the fixed core 10A and the movable core 10B, and the movable core 10B is biased by the return spring 29 in a direction moving upward away from the fixed core 10A, as shown in Fig. 3. In this state, the movable contact portions 23b, 23c of the movable contactor 23 are upwardly separated from the fixed contact portions 22a, 22b of the fixed contactor 22, and the contacts are in an open state.

[0050] When a single-phase AC current is supplied to the electromagnetic coil 28 from this open contact state, an attractive force is generated between the fixed core 10A and the movable core 10B, and the movable core 10B is attracted downward against the return spring 29. As a result, the movable contactor 23 supported by the contactor holder 41 descends, and the movable contact portions 23b, 23c come into contact with the fixed contact portions 22a, 22b of the fixed contactor 22 by the contact pressure of the contact spring 43, and the contacts are brought into a closed state.

[0051] When the contacts are in a closed state, for example, a current input from an external connection terminal 44a of the fixed contactor 22 connected to a DC power source (not shown) is supplied to the movable contact portion 23b of the movable contactor 23 through the conductive portion 22c and the fixed contact portion 22a. The current supplied to the movable contact portion 23b is supplied to the fixed contact portion 22b in the conductive portion 22d of the fixed contactor 22 through the conductive portion 23a and the movable contact portion 23c. The current supplied to the fixed contact portion 22b is supplied to an external load through the conductive portion 22d and the external connection terminal 44b, thereby forming an electric current path.

[0052] In the electromagnetic contactor 100, the members other than the fixed core 10A and the movable core 10B are not limited to the above-mentioned configuration, and may have other configurations.

[0053] <Steel manufacturing method> A method for manufacturing the steel material 1 of this embodiment will be described. In the method for manufacturing the steel material 1 of this embodiment, NH 3 In a gas atmosphere, the surface of the base material 2 of the steel material 1 is irradiated with laser light in a specific irradiation range, and the base material 2 is heated for 3 to 9 seconds in a state where the surface temperature of the base material 2 is 1000°C to 1400°C. 4 N, Fe 2~3 The steel material 1 has a first layer 31, a second layer 32, and a third layer 33, each of which is composed of at least one of N and CrN, and a structure containing martensite with an area ratio of 90% or more relative to a square region of 15 μm×200 μm in a cross section perpendicular to the surface of the steel material 1 is formed from the interface between the first layer 31 and the second layer 32 to a depth of 15 μm. This manufacturing method allows the steel material 1 to have high hardness, and can prevent brittle fracture due to excessive hardness. Therefore, the steel material 1 can exhibit excellent wear resistance. In particular, the steel material 1 can exhibit excellent wear resistance even when used in an electromagnetic core of an electromagnetic contactor and the steel materials 1 collide with each other repeatedly.

[0054] Furthermore, by irradiating the laser light to a specific irradiation area, it is possible to form a structure including the above-mentioned first layer 31 and martensite only in the specific area of ​​the surface of the base material 2 where nitriding treatment is performed, i.e., the specific area where wear resistance is required, thereby reducing the manufacturing cost of the steel material 1.

[0055] Furthermore, in the manufacturing method of the steel material 1 of this embodiment, nitriding treatment is performed by irradiating laser light under specified conditions, and a structure including the above-mentioned first layer 31 and martensite can be formed, making it easy to manufacture.

[0056] When the steel material 1 is plate-shaped, the end face of the plate-shaped base material 2 may be irradiated with laser light in a specific irradiation range, thereby heating the base material 2 for 3 to 9 seconds until the surface temperature of the base material 2 reaches 1000°C to 1400°C.

[0057] In the manufacturing method of the steel material 1 of this embodiment, the base material 2 may be an electromagnetic steel sheet, and in this case, it is preferable to remove the insulating coating on the surface of the electromagnetic steel sheet to expose the base material before irradiating the surface of the electromagnetic steel sheet with laser light. This makes it possible to irradiate the base material of the electromagnetic steel sheet with laser light and perform nitriding treatment in a state where the insulating coating that inhibits nitriding has been removed, so that the steel material 1 has high hardness and can exhibit excellent wear resistance even when the base material 2 is an electromagnetic steel sheet.

[0058] <Manufacturing method of electromagnetic core> A method for manufacturing an electromagnetic core 10 of this embodiment, which is made of a laminated body of multiple laminated electromagnetic steel sheets, will be described. Fig. 4 is a schematic diagram for explaining a method for manufacturing an electromagnetic core 10 according to one embodiment. A laminated body 20 of electromagnetic steel sheets as a base material 2 is placed on a stage 54 in a vacuum chamber 51, for example, and is then evacuated. 3 The atmosphere in the vacuum chamber 51 is replaced with a gas. A sapphire glass 52 for transmitting laser and a flange 53 for fixing the sapphire glass 52 may be provided on the upper surface of the vacuum chamber 51. A semiconductor laser 55 is fixed above the vacuum chamber 51.

[0059] In the manufacturing method of the electromagnetic core 10 of this embodiment, the insulating coating on the surface of the laminate 20 is removed to expose the base material, and then NH 3 In a gas atmosphere, the base material of the laminate 20 is irradiated with laser light in a specific irradiation range, and the laminate 20 is heated for 3 to 9 seconds in a state where the surface temperature of the laminate 20 is 1000°C to 1400°C. 4 N, Fe 2~3 The first layer 31, the second layer 32, and the third layer 33 are formed from at least one of N and CrN, and a structure containing martensite with an area ratio of 90% or more to a square region of 15 μm×200 μm in a cross section perpendicular to the surface of the electromagnetic core 10 is formed from the interface between the first layer 31 and the second layer 32 to a depth of 15 μm. This manufacturing method allows the electromagnetic core 10 to have high hardness, and can prevent brittle fracture due to excessive hardness. Therefore, the steel material 1 can exhibit excellent wear resistance. In particular, the electromagnetic core 10 can exhibit excellent wear resistance even when used in an electromagnetic contactor and the electromagnetic cores 10 collide with each other repeatedly.

[0060] Furthermore, by irradiating laser light onto a specific irradiation area, it is possible to form a structure including the above-mentioned first layer 31 and martensite only in the specific area of ​​the surface of the laminate 20 where nitriding treatment is performed, i.e., the specific area where wear resistance is required, thereby reducing the manufacturing cost of the electromagnetic core 10.

[0061] In the manufacturing method of the electromagnetic core 10 of this embodiment, as shown in Fig. 4, when the laminate 20 has three protrusions 2a, 2b, 2c arranged so as to have an E-shaped shape in a plan view, and the three protrusions 2a, 2b, 2c include side protrusions 2a, 2b located on both sides and a central protrusion 2c located in the center, it is preferable to irradiate the surfaces S1, S2 of the side protrusions 2a, 2b with laser light, and not irradiate the surface S3 of the central protrusion 2c with laser light. With this manufacturing method, only the surfaces S1, S2 of the side protrusions 2a, 2b, which become the contact surfaces 7a, 7b (see Fig. 2) of the electromagnetic core 10, among the surfaces of the laminate 20, are irradiated with laser light to perform nitriding treatment, and the above-mentioned first layer 31 and a structure including martensite can be formed. Therefore, the contact surfaces 7a, 7b of the electromagnetic core 10 have high hardness and can exhibit excellent wear resistance even when the electromagnetic core 10 is used in an electromagnetic contactor and the electromagnetic cores 10 collide repeatedly with each other.

[0062] The laser irradiation range is preferably the same as the area of ​​the surface S1 of the side convex portion 2a and the surface S2 of the side convex portion 2b. This allows the laser light to be irradiated only to the surfaces S1 and S2 of the side convex portions 2a and 2b to perform nitriding treatment and form the above-mentioned first layer 31 and a structure including martensite, so that the contact surfaces 7a and 7b of the electromagnetic core 10 have high hardness over the entire surface and can exhibit superior wear resistance even when the electromagnetic core 10 is used in an electromagnetic contactor and the electromagnetic cores 10 collide with each other repeatedly.

[0063] Furthermore, since all of the irradiated laser light can be used for nitriding the surfaces S1, S2 of the side convex portions 2a, 2b, which become the contact surfaces 7a, 7b of the electromagnetic core 10, the electromagnetic core 10 having the contact surfaces 7a, 7b and the non-contact surface 7c can be manufactured at low cost. EXAMPLES

[0064] Next, examples of the present invention will be described, but the present invention is not limited to the examples described below.

[0065] First, the insulating coating on the surface of the laminate of multiple stacked electromagnetic steel sheets (electromagnetic iron core before nitriding treatment) was removed to expose the base material. The laminate of electromagnetic steel sheets was then placed on a stage in a vacuum chamber, and after the vacuum was drawn with a vacuum pump, nitriding gas (NH 3 A nitrogen gas (nitride gas) was flowed into the vacuum chamber at a flow rate of 1.2 L / min, and the atmosphere in the vacuum chamber was replaced with nitriding gas. After that, a semiconductor laser (wavelength: 940 nm to 987 nm) was used to irradiate the base surface of the laminate with laser light at an output of 2500 W, with an irradiation area of ​​8 mm x 15 mm, the same as the area of ​​the contact surface of the electromagnetic core, to heat the laminate for 6 seconds at a surface temperature of about 1300°C, thereby obtaining a nitrided electromagnetic core.

[0066] The nitrogen concentration versus depth from the surface of the obtained electromagnetic core (direction perpendicular to the surface) was measured by glow discharge optical emission spectroscopy (GD-OES). Figure 5 shows a graph illustrating the relationship between the depth from the surface of the electromagnetic core of the example and the nitrogen concentration. In addition, a cross section perpendicular to the surface of the obtained electromagnetic core was observed with a scanning electron microscope (SEM). Figure 6 shows an SEM observation image showing a cross section of the electromagnetic core of the example.

[0067] As shown in Figures 5 and 6, it was confirmed that a first layer having a thickness of 3.5 μm was formed, the region below the first layer where the nitrogen concentration was 3 at% or more and 30 at% or less was defined as the second layer, and the region where the nitrogen concentration was 0.2 at% or more and less than 3 at% was defined as the third layer, and a second layer having a thickness of 9.8 μm was formed, and a third layer having a thickness of 36.7 μm was formed below the second layer.

[0068] 6, an acicular martensite structure was observed from the interface between the first layer 31 and the second layer 32 to a depth of 15 μm. A square region of 15 μm × 200 μm was observed at a magnification of 700 times, and the area ratio of martensite was calculated to be 90% by performing image analysis on the photographed structure.

[0069] Furthermore, the first, second and third layers of the obtained electromagnetic core were analyzed by X-ray diffraction (XRD), and it was found that the first layer contained Fe2~3 N and Fe 4 The formation of γ-FeN was confirmed in the third layer. 0.095 The formation of was confirmed.

[0070] Next, the micro Vickers hardness of the obtained electromagnetic core with respect to the depth from the surface was measured using a micro Vickers tester under conditions of a load of 20 g and a load time of 8 seconds. The hardness of the second layer was measured at a position from the interface between the first layer 31 and the second layer 32 that was 2 / 3 (6.5 μm) of the thickness of the second layer, and was 420 Hv. The hardness of the third layer was measured at a position from the surface of the third layer on the second layer side that was 2 / 3 (24.5 μm) of the thickness of the third layer, and was 280 Hv.

[0071] The steel material 1 of this embodiment can be applied to electromagnetic cores and electromagnetic contactors, as well as mechanical parts having sliding parts.

[0072] As described above, the embodiment has been described, but the above embodiment is presented as an example, and the present invention is not limited to the above embodiment. The above embodiment can be implemented in various other forms, and various combinations, omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]

[0073] 1 Steel material 2 Base material 3. Nitriding layer 31 1st layer 32 2nd layer 33 3rd layer 2a, 2b, 4a, 4b, 14a, 14b, 15a, 15b Side protrusions 2c, 4c, 14c, 15c central convex part 5-pin 6 Bottom 7a, 7b, 17a, 17b, 18a, 18b contact surface 7c, 17c, 18c non-contact surface 10 Electromagnetic core 10A fixed core 10B Movable core 20 Laminate 51 Vacuum Chamber 52 Sapphire glass 53 Flange 54 Stages 55 Semiconductor Laser S1, S2, S3 surface 100 Magnetic contactor

Claims

1. A steel material having a nitride layer on its surface, the nitride layer includes a first layer, a second layer, and a third layer provided in this order from the surface, The first layer is Fe 4 N, Fe 2~3 N and CrN, a nitrogen concentration in the second layer is equal to or greater than 3 at% and equal to or less than 30 at%, and a nitrogen concentration in the third layer is equal to or greater than 0.2 at% and less than 3 at%, A steel material in which the structure from the interface between the first layer and the second layer to a depth of 15 μm contains martensite in an area ratio of 90% or more relative to a 15 μm x 200 μm square region in a cross section perpendicular to the surface.

2. 2. The steel material according to claim 1, wherein the structure in the second layer contains martensite in an area ratio of 90% or more relative to a 15 μm×200 μm square region in a cross section perpendicular to the surface.

3. The steel material according to claim 2 , wherein the first layer, the second layer, and the third layer each have a thickness of 1 μm or more.

4. 4. The steel material according to claim 3, wherein the first layer has a maximum thickness of 10 μm.

5. 5. The steel material according to claim 4, wherein the second layer has a maximum thickness of 15 μm.

6. 6. The steel material according to claim 5, wherein the third layer has a maximum thickness of 45 μm.

7. The steel material according to claim 6, wherein the second layer has a hardness of 420 Hv or more, and the third layer has a hardness of 250 Hv or more and less than 420 Hv.

8. The steel material according to claim 7, wherein the first layer has a hardness of 1000 Hv or more.

9. The steel material according to any one of claims 1 to 8, which is in the form of a plate.

10. The steel material according to claim 9, which is magnetic.

11. An electromagnetic core formed by laminating a plurality of the steel materials according to claim 10.

12. An electromagnetic contactor comprising the electromagnetic core according to claim 11.

13. The electromagnetic core includes a fixed core and a movable core movably disposed opposite the fixed core, the fixed core and the movable core have contact surfaces that come into contact when the fixed core and the movable core come into contact with each other, 13. The electromagnetic contactor of claim 12, wherein the surface of the steel material constitutes the contact surface.

14. The fixed core and the movable core each have three protrusions that are E-shaped in a plan view, The three protrusions include side protrusions located on both sides and a central protrusion located in the center, The side protrusion includes the contact surface, The electromagnetic contactor according to claim 13 , wherein when the fixed core and the movable core come into contact with each other, the central protrusions do not come into contact with each other.

15. N.H. 3 In a gas atmosphere, the surface of the base material of the steel material is irradiated with laser light in a specific irradiation range, and the base material is heated for 3 to 9 seconds in a state where the surface temperature of the base material is 1000°C to 1400°C. 4 N, Fe 2~3 A method for manufacturing a steel material, comprising forming a first layer, a second layer, and a third layer each composed of at least one of N and CrN, and forming a structure containing martensite in an area ratio of 90% or more to a 15 μm x 200 μm square region in a cross section perpendicular to the surface of the steel material, from an interface between the first layer and the second layer to a depth of 15 μm.

16. The base material is an electromagnetic steel sheet, The method for producing a steel material according to claim 15, further comprising removing an insulating coating on the surface of the electromagnetic steel sheet to expose the base material before irradiating the surface of the electromagnetic steel sheet with the laser light.

17. A method for manufacturing an electromagnetic core made of a laminate of multiple electromagnetic steel sheets, comprising the steps of: The insulating coating on the surface of the laminate was removed to expose the base material, and then NH 3 In a gas atmosphere, the base material of the laminate is irradiated with laser light in a specific irradiation range, and the laminate is heated for 3 to 9 seconds in a state where the surface temperature of the laminate is 1000° C. to 1400° C., and Fe 4 N, Fe 2~3 A manufacturing method for an electromagnetic core, comprising forming a first layer, a second layer, and a third layer each composed of at least one of N and CrN, and forming a structure containing martensite with an area ratio of 90% or more for a 15 μm x 200 μm square region in a cross section perpendicular to the surface of the electromagnetic core, from the interface between the first layer and the second layer to a depth of 15 μm.

18. The laminate has three protruding portions that are provided so as to have an E-shape in a plan view, The three protrusions include side protrusions located on both sides and a central protrusion located in the center, The method for manufacturing an electromagnetic core according to claim 17 , wherein the laser light is irradiated onto surfaces of the side convex portions, and the laser light is not irradiated onto a surface of the central convex portion.

Citation Information

Patent Citations

  • Magnetic steel sheet-nitriding method and magnetic steel sheet having high-hardness and high magnetic characteristic

    JP2005226118A